Study on consequences for interaction of myricetin with canagliflozin: A special attention to pharmacokinetics and pharmacodynamics of drug - Naga Raju Kandukoori; Deepika B; Kiranmai Mandava (Faculty of Pharmacy, Mahidol University, 2023)
The metabolism of most antidiabetic drugs is initiated by Cytochrome P-450 (CYP) enzymes present in the human body. The result of this metabolism can be a formation of either active metabolites or inactive metabolites. There is possibility of alteration in the activity of CYP enzymes due to some phytoconstituents which are present in vegetables, fruits and ayurvedic products. In the present research, the effect of myricetin on pharmacokinetics and pharmacodynamics of canagliflozin was studied. Both normal and diabetic rats were used for study. Rats were categorized into different groups. One group received drug alone where as other groups administered a drug in combination with myricetin. Treatment was continued for 8 days and then blood samples were collected and analysed. The pharmacokinetic parameters like Cmax, tmax, AUC, MRT, Vd and ClT were estimated for all groups and compared with each other. The mean blood glucose levels were noted before and after treatments and compared among diabetic groups. Results revealed a fact that the myricetin has inhibited the activity of CYP 2C8, CYP 2C9 and CYP 3A4 enzymes, thereby causing to decreased metabolism of drug which ultimately resulted in the increase of Cmax and AUC. The Myricetin could raise the antidiabetic effect of canagliflozin.